Spontaneous Spine Fracture in Patient with Ankylosing Spondylitis under Spinal Anesthesia: A Case Report and Review of the Literature - Ul-Oh Jeung; Dae-Chang Joo; Sung-Kyu Kim; Chae-Jin Im (Medicina, 2021)
Factures in ankylosing spondylitis (AS) patients tend to occur due to the absence of motion between vertebrae, poor bone quality, and a long lever arm that generates extension force. However, most patients have a history of at least minor trauma. The aim of this report was that a vertebral fracture in a patient with AS can be caused not only by minor trauma, but also by position changes or maintenance of position for examination due to structural weakness. A 75-year-old woman with AS visited her local hospital on foot for back pain. She usually had back pain. However, she had increased back pain after falling over three weeks prior. In plain radiographs, no fracture was apparent. The doctor tried to perform magnetic resonance imaging (MRI) for further evaluation. However, several attempts of MRI failed due to continuous movement arising from pain. As a result, MRI was performed under spinal anesthesia for pain control. However, complete paraplegia developed during the MRI examination. MRI showed extension-type vertebral fracture with displacement and the patient was transferred to our hospital. We performed emergency posterior fusion, but neurological symptoms did not improve. This case suggests the need for careful positioning, sedation, or anesthesia when performing an examination or surgery in AS patients. We recommend that all patients with AS should be carefully positioned at all times during testing or surgery.